Surgical perspective in pseudoaneurysm of peripheral arteries: a better limb salvage option - Sinha, Lakshmi; Kumar, Sanjeev; Ranjan, Nishit; ., Rituraj (International Surgery Journal, 2021)
Aneurysm involve all three layers of vessel wall. Psudoaneurysm also known as false aneurysm is a collection of blood that forms between the two outer layers of an artery. Femoral and popliteal artery aneurysms account for more than 90% of peripheral aneurysms, with popliteal artery aneurysms being the most common (70%). The estimated incidence of femoral and popliteal aneurysms is approximately 7/100,000 men and 1/100,000 women. Femoral aneurysms usually involve the common femoral artery but may occasionally extend or be limited to the superficial femoral artery (SFA) in the midthigh. Femoral and popliteal aneurysms are commonly associated with other aneurysms, with approximately 80% of patients having multiple aneurysms. Femoral and popliteal aneurysms show a high incidence of thromboembolic complications, which can result in limb loss. Pseudoaneurysm, if left untreated can result in deadly limb loss.